2022
DOI: 10.1130/b36318.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Mesozoic intracontinental deformation and magmatism in the Chinese Tianshan and adjacent areas, Central Asia

Abstract: The Tianshan Range−Junggar Basin−Kalamaili Range system represents the southwestern Central Asian Orogenic Belt and is a natural laboratory for studying intracontinental deformation processes. Its current topography is a product of the far-field effects of the Cenozoic India-Asia collision. However, the Mesozoic topographic and tectonic evolution of the Tianshan and Kalamaili Ranges and their impacts on the Junggar Basin remain enigmatic due to the scarcity of data. Here, we present a comprehensive synthesis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…A new age group component of 140–170 Ma now accounts for 20–40% of the total zircon population (Figure 11f–h), and the source is probably associated with the ongoing Late Jurassic “Yanshanian” magmatic activities. Late Jurassic–Early Cretaceous tectonic activity induced intense uplift of the Tianshan Mountains and magmatic activity (Morin et al, 2018; Wang et al, 2022; Zhu, Wang, Cao, & Wang, 2020; Zhu, Wang, Lu, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new age group component of 140–170 Ma now accounts for 20–40% of the total zircon population (Figure 11f–h), and the source is probably associated with the ongoing Late Jurassic “Yanshanian” magmatic activities. Late Jurassic–Early Cretaceous tectonic activity induced intense uplift of the Tianshan Mountains and magmatic activity (Morin et al, 2018; Wang et al, 2022; Zhu, Wang, Cao, & Wang, 2020; Zhu, Wang, Lu, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During the Early Jurassic through early Middle Jurassic, the boundary of the basin was at least near the southern edge of the Houxia area, which is now located in the intermontane region, and there was no obvious geographical separation at this time (Fang et al, 2005) and the source is probably associated with the ongoing Late Jurassic "Yanshanian" magmatic activities. Late Jurassic-Early Cretaceous tectonic activity induced intense uplift of the Tianshan Mountains and magmatic activity (Morin et al, 2018;Wang et al, 2022;Zhu, Wang, Cao, & Wang, 2020;Zhu, Wang, Lu, et al, 2020).…”
Section: Evolution Of the Source Areamentioning
confidence: 99%
“…Based on a summary of published detrital zircon U-Pb data and sedimentary analyses, it is suggested that the North Tianshan was the main source terrane for the sediments in the southern Junggar Basin during the Jurassic (e.g. Fang et al 2019;Wang et al 2022). Hence, the Late Triassic-Middle Jurassic AFT cooling ages were not only recorded by the basement rocks in the Bogda Shan (Supplementary Table S3), the neighbouring basins also received coeval thermochronological signals.…”
Section: Thermochronological Datamentioning
confidence: 99%
“…On the other hand, the Chinese Tianshan belt and neighbouring basins experienced varying degrees of deformation during the Cretaceous generally under a contractional setting (e.g. Zhu et al 2004Zhu et al , 2006Yang et al 2017;Wang et al 2022;He et al 2022aHe et al , 2022b. In the eastern and southern Junggar Basin, the Jurassic strata were deformed and folded as revealed by the seismic profile data (e.g.…”
Section: Mesozoic Building Of the Bogda-balikun-harlik Mountain Chainmentioning
confidence: 99%
See 1 more Smart Citation